2010
DOI: 10.1371/journal.pone.0011288
|View full text |Cite
|
Sign up to set email alerts
|

The Ability to Generate Senescent Progeny as a Mechanism Underlying Breast Cancer Cell Heterogeneity

Abstract: BackgroundBreast cancer is a remarkably heterogeneous disease. Luminal, basal-like, “normal-like”, and ERBB2+ subgroups were identified and were shown to have different prognoses. The mechanisms underlying this heterogeneity are poorly understood. In our study, we explored the role of cellular differentiation and senescence as a potential cause of heterogeneity.Methodology/Principal FindingsA panel of breast cancer cell lines, isogenic clones, and breast tumors were used. Based on their ability to generate sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…It was reported that senescence in ERα-dependent breast cancer cells induced by tamoxifen appeared to result from the downregulation of survival signals generated by the transcriptional activity of ERα, indicating an anti-senescence role of ERα in breast cancer [8]. Consistently, our results demonstrated that the knockdown of ERα expression with the transfection of the siRNAs induced senescence-like phenotypes in ZR-75-1 and MCF-7 cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was reported that senescence in ERα-dependent breast cancer cells induced by tamoxifen appeared to result from the downregulation of survival signals generated by the transcriptional activity of ERα, indicating an anti-senescence role of ERα in breast cancer [8]. Consistently, our results demonstrated that the knockdown of ERα expression with the transfection of the siRNAs induced senescence-like phenotypes in ZR-75-1 and MCF-7 cells.…”
Section: Discussionsupporting
confidence: 89%
“…Cellular senescence is one of the mechanisms that normal cells use to avoid carcinogenesis [7]. It was demonstrated that tamoxifen can induce a senescent phenotype in several ERα+ breast cancer cells lines [8], which suggested that ERα might play an important role in the regulation of senescence and growth inhibition in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Huh-7 cell line is used in lab since 1995 and was last tested for authenticity in 2010 (originally from Jack Wands Lab at Massachusetts General Hospital, Boston, MA). All breast cancer cell lines have been tested and authenticated by short tandem repeat profiling in September 2009 and February 2012, as described previously [25]. SK-BR-3 cells were grown in McCoy’s 5A medium.…”
Section: Methodsmentioning
confidence: 99%
“…SK-BR-3 cells were grown in McCoy’s 5A medium. MDA-MB-361, T47D, MCF-7, BT-474 and Huh-7 cells were grown in Dulbecco’s Modified Eagle Medium (DMEM), as described [25,26]. Hybridomas were grown in RPMI 1640, DMEM or Serum Free Media (SFM) from Hyclone (IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of cell clones generated from single cells of breast carcinoma tumor cell lines in vitro showed that within 12 different cells lines tested there were two groups. One group (5 cell lines) produced senescent cells (positive for SA-β-Gal/negative for BrdU incorporation) with high frequency (5-40%) whereas the other group produced less that 5% of senescent cells (Mumcuoglu et al, 2010). Based on these features, the authors classified all breast cell lines studied as senescent cell progenitor (SCP) and immortal cell progenitor (ICP) cell subtypes.…”
Section: Properties Of Stem Cells and Cscs: Similarities And Differencesmentioning
confidence: 99%